Ratio Problem!

Geometry Level 3

In right A B C , m A B C = 3 0 , A D = x , D B = 3 x \triangle{ABC}, m\angle{ABC} = 30^{\circ}, \overline{AD} = x, \overline{DB} = 3x and the quarter of the circle has radius C E = 2 x 2 \overline{CE} = 2x - 2 .

Find A 2 A 1 \dfrac{A_{2}}{A_{1}} .


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

David Vreken
Jan 7, 2021

Let the point to the left of E E be H H , and let B E = y BE = y .

Since A B C = 30 ° \angle ABC = 30° and A B = 4 x AB = 4x , from A B C \triangle ABC we have A C = 2 x AC = 2x and B C = 2 3 x = 2 x 2 + y BC = 2\sqrt{3}x = 2x - 2 + y .

By the tangent-secant theorem , ( 3 x ) 2 = y ( 4 x 4 + y ) (3x)^2 = y(4x - 4 + y) .

These two equations solve to x = 4 + 2 3 x = 4 + 2\sqrt{3} and y = 6 + 4 3 y = 6 + 4\sqrt{3} .

That means A C = 2 x = 2 ( 4 + 2 3 ) = 8 + 4 3 AC = 2x = 2(4 + 2\sqrt{3}) = 8 + 4\sqrt{3} and E C = 2 x 2 = 2 ( 4 + 2 3 ) 2 = 6 + 4 3 EC = 2x - 2 = 2(4 + 2\sqrt{3}) - 2 = 6 + 4\sqrt{3} .

Since H B E = 30 ° \angle HBE = 30° and B E = y = 6 + 4 3 BE = y = 6 + 4\sqrt{3} , from H B E \triangle HBE we have H E = 3 3 ( 6 + 4 3 ) = 4 + 2 3 = x = A D HE = \frac{\sqrt{3}}{3}(6 + 4\sqrt{3}) = 4 + 2\sqrt{3} = x = AD .

By the Pythagorean Theorem on A D C \triangle ADC , D C = A C 2 A D 2 = ( 8 + 4 3 ) 2 ( 4 + 2 3 ) 2 = 6 + 4 3 = E C DC = \sqrt{AC^2 - AD^2} = \sqrt{(8 + 4\sqrt{3})^2 - (4 + 2\sqrt{3})^2} = 6 + 4\sqrt{3} = EC .

By the Pythagorean Theorem on H E C \triangle HEC , H C = H E 2 + E C 2 = ( 4 + 2 3 ) 2 + ( 6 + 4 3 ) 2 = 8 + 4 3 = A C HC = \sqrt{HE^2 + EC^2} = \sqrt{(4 + 2\sqrt{3})^2 + (6 + 4\sqrt{3})^2} = 8 + 4\sqrt{3} = AC .

By the Pythagorean Theorem on H D C \triangle HDC , H D = H C 2 D C 2 = ( 8 + 4 3 ) 2 ( 6 + 4 3 ) 2 = 4 + 2 3 = A D = H E HD = \sqrt{HC^2 - DC^2} = \sqrt{(8 + 4\sqrt{3})^2 - (6 + 4\sqrt{3})^2} = 4 + 2\sqrt{3} = AD = HE .

Since H D = A D = H E HD = AD = HE , A C = H C AC = HC , and D C = E C DC = EC , triangles A D C \triangle ADC , H D C \triangle HDC and H E C \triangle HEC are all congruent to each other by SSS congruency.

By corresponding parts of congruent triangles, A C D = H C D = H C E \angle ACD = \angle HCD = \angle HCE .

Since A 2 A_2 spans exactly twice the triangles and angles of A 1 A_1 , A 2 A 1 = 2 \cfrac{A_2}{A_1} = \boxed{2} .

Rocco Dalto
Jan 7, 2021

A F = 2 x ( 2 x 2 ) = 2 , G D = 3 2 x , A G = x 2 AF = 2x - (2x - 2) = 2, \overline{GD} = \dfrac{\sqrt{3}}{2}x, \overline{AG} = \dfrac{x}{2} \implies

( C D ) 2 = 4 ( x 1 ) 2 = 16 x 2 32 x + 16 = ( 2 x x 2 ) 2 + 3 4 x 2 = 12 x 2 x 2 8 x + 4 = 0 x = 4 ± 2 3 (\overline{CD})^2 = 4(x - 1)^2 = 16x^2 - 32x + 16 = (2x - \dfrac{x}{2})^2 + \dfrac{3}{4}x^2 = 12x^2 \implies x^2 - 8x + 4 = 0 \implies x = 4 \pm 2\sqrt{3}

x = 4 2 3 2 ( x 1 ) = 2 ( 3 2 3 ) < 0 x = 4 - 2\sqrt{3} \implies 2(x - 1) = 2(3 - 2\sqrt{3}) < 0 \therefore choose x = 4 + 2 3 x = 4 + 2\sqrt{3}

\implies radius r = 2 x 2 = 2 ( 3 + 2 3 ) r = 2x - 2 = 2(3 + 2\sqrt{3})

For A 2 A_{2} :

Let θ = m D C E \theta = m\angle{DCE}

tan ( θ ) = 3 θ = π 3 A s e c t o r C D E = 1 2 θ r 2 = 1 2 ( π 3 ) ( 4 ) ( 3 + 2 3 ) 2 = \implies \tan(\theta)= \sqrt{3} \implies \theta = \dfrac{\pi}{3} \implies A_{sector{CDE}} = \dfrac{1}{2}\theta r^2 = \dfrac{1}{2}(\dfrac{\pi}{3})(4)(3 + 2\sqrt{3})^2 =

2 π ( 7 + 4 3 ) 2\pi(7 + 4\sqrt{3})

and A C D I = 1 2 ( 3 x 2 ) ( 3 2 x ) = 3 3 8 x 2 = A_{\triangle{CDI}} = \dfrac{1}{2}(\dfrac{3x}{2})(\dfrac{\sqrt{3}}{2}x) = \dfrac{3\sqrt{3}}{8}x^2 = 3 3 8 ( 4 + 2 3 ) 2 \dfrac{3\sqrt{3}}{8}(4 + 2\sqrt{3})^2 = 3 3 2 ( 7 + 4 3 ) = \dfrac{3\sqrt{3}}{2}(7 + 4\sqrt{3})

Let R 2 R_{2} be region D E I A R 2 = A s e c t o r C D E A C D I = ( 7 + 4 3 ) ( 4 π 3 3 ) 2 DEI \implies A_{R_{2}} = A_{sector{CDE}} - A_{\triangle{CDI}} = \dfrac{(7 + 4\sqrt{3})(4\pi - 3\sqrt{3})}{2}

B C = 2 3 x B E = 2 3 x ( 2 x 2 ) = 2 ( ( 3 1 ) x + 1 ) = \overline{BC} = 2\sqrt{3}x \implies \overline{BE} = 2\sqrt{3}x - (2x - 2) = 2((\sqrt{3} - 1)x + 1) =

2 ( 2 3 + 3 ) 2(2\sqrt{3} + 3) and A D G H B E 1 3 = H E 2 ( 2 3 + 3 ) H E = 4 3 + 6 3 = \triangle{ADG} \sim \triangle{HBE} \implies \dfrac{1}{\sqrt{3}} = \dfrac{\overline{HE}}{2(2\sqrt{3} + 3)} \implies \overline{HE} = \dfrac{4\sqrt{3} + 6}{\sqrt{3}} = 4 + 2 3 = x 4 + 2\sqrt{3} = x and D I = 3 x 2 = 3 ( 2 + 3 ) DI = \dfrac{3x}{2} = 3(2 + \sqrt{3}) and I E = C E C I = IE = \overline{CE} - \overline{CI} =

( 4 3 2 ) x 2 = 3 + 2 3 (\dfrac{4 - \sqrt{3}}{2})x - 2 = 3 + 2\sqrt{3} \implies area of trapezoid

A D H E I = 1 2 ( 5 ) ( 2 + 3 ) ( 3 + 2 3 ) = 5 2 ( 12 + 7 3 ) A_{DHEI} = \dfrac{1}{2}(5)(2 + \sqrt{3})(3 + 2\sqrt{3}) = \dfrac{5}{2}(12 + 7\sqrt{3})

A 2 = A D H E I A R 2 = 48 + 28 3 ( 14 + 8 3 ) π = 2 ( 24 + 14 3 ( 7 + 4 3 ) π ) \implies \boxed{A_{2} = A_{DHEI} - A_{R_{2}} = 48 + 28\sqrt{3} - (14 + 8\sqrt{3})\pi = 2(24 + 14\sqrt{3} - (7 + 4\sqrt{3})\pi)}

For A 1 : A_{1}:

m F C D = π 6 A s e c t o r C D F = 1 2 ( π 6 ) ( 4 ) ( 3 + 2 3 ) 2 = π ( 7 + 4 3 ) m\angle{FCD} = \dfrac{\pi}{6} \implies A_{sector{CDF}} = \dfrac{1}{2}(\dfrac{\pi}{6})(4)(3 + 2\sqrt{3})^2 = \pi(7 + 4\sqrt{3})

and A D G C = 3 3 2 ( 7 + 4 3 ) A_{\triangle{DGC}} = \dfrac{3\sqrt{3}}{2}(7 + 4\sqrt{3})

Let R 1 R_{1} be region F D G A R 1 = A s e c t o r C D F A D G C = FDG \implies A_{R_{1}} = A_{sector{CDF}} -A_{\triangle{DGC}} = ( 7 + 4 3 ) ( 2 π 3 3 ) 2 \dfrac{(7 + 4\sqrt{3})(2\pi - 3\sqrt{3})}{2}

and A A D G = 3 8 x 2 = 3 2 ( 7 + 4 3 ) A_{\triangle{ADG}} = \dfrac{\sqrt{3}}{8}x^2 = \dfrac{\sqrt{3}}{2}(7 + 4\sqrt{3})

A 1 = A A D G A R 1 = ( 7 + 4 3 ) ( 2 3 π ) = 24 + 14 3 ( 7 + 4 3 ) π \implies \boxed{A_{1} = A_{\triangle{ADG}} - A_{R_{1}} = (7 + 4\sqrt{3})(2\sqrt{3} - \pi) = 24 + 14\sqrt{3} - (7 + 4\sqrt{3})\pi}

A 2 A 1 = 2 \implies \dfrac{A_{2}}{A_{1}} = \boxed{2} .

Hongqi Wang
Jan 9, 2021

E H B C EH \perp BC and intersects A B AB at H H :

C D = r = C E R T C D H R T C E H E C H = D C H = 1 2 B C D = 30 ° R T C D H R T C D A R T C E H A 2 = 2 A 1 A 2 A 1 = 2 \begin{aligned} &CD = r = CE \\ \implies &RT\triangle CDH \cong RT\triangle CEH \\ \therefore &\angle ECH = \angle DCH = \dfrac 12 \angle BCD = 30\degree \\ \implies &RT\triangle CDH \cong RT\triangle CDA \cong RT\triangle CEH \\ \implies &A_2 = 2 A_1 \\ \therefore &\dfrac {A_2}{A_1} = \boxed{2} \end{aligned}

Label the two parallel lines to C A CA be E F EF and D G DG and D H DH the perpendicular line to C A CA .. By Pythagorean theorem ,

C G 2 + D G 2 = C D 2 Note that C G = D H ( A D cos 3 0 ) 2 + ( D B sin 3 0 ) 2 = ( 2 x 2 ) 2 3 4 x 2 + 9 4 x 2 = 4 x 2 8 x + 4 x 2 8 x + 4 = 0 ( x 4 ) 2 = 12 x = 2 3 + 4 \begin{aligned} \blue{CG}^2+DG^2 & = CD^2 & \small \blue{\text{Note that }CG = DH} \\ (AD \cdot \cos 30^\circ)^2 + (DB \cdot \sin 30^\circ)^2 & = (2x-2)^2 \\ \frac 34 x^2 + \frac 94 x^2 & = 4x^2 - 8x + 4 \\ x^2 - 8x + 4 & = 0 \\ (x-4)^2 & = 12 \\ \implies x & = 2\sqrt 3 + 4 \end{aligned}

Then C E = 2 x 2 = 4 3 + 6 CE=2x-2 = 4 \sqrt 3 + 6 and B C = A B cos 3 0 = 2 3 x = 8 3 + 12 = 2 C E BC = AB \cdot \cos 30^\circ = 2 \sqrt 3 x = 8\sqrt 3 + 12 = 2 \cdot CE . Then the ratio of lengths B E : B G : B C = 2 : 3 : 4 BE:BG:BC = 2:3:4 . Let the area of A D H \triangle ADH , [ADH] = A). then [ B E F ] = 4 A [BEF]=4A , [ A D G C ] = 12 A [ADGC] = 12A , A D G C = 7 A ADGC = 7A , [ D G C H ] = 6 A [DGCH] = 6A , and [ C D H ] = 3 A [CDH] = 3A . Let r = 2 x 2 r = 2x-2 . Then we have:

{ A 1 + A 2 = [ A F E C ] π r 2 4 = 12 a π r 2 4 . . . ( 1 ) A 2 = [ A D G C ] [ C D H ] π r 2 12 = 4 A π r 2 12 . . . ( 2 ) \begin{cases} A_1 + A_2 = [AFEC] - \dfrac {\pi r^2}4 = 12a - \dfrac {\pi r^2}4 & ...(1) \\ A_2 = [ADGC]-[CDH] - \dfrac {\pi r^2}{12} = 4A - \dfrac {\pi r^2}{12} & ... (2) \end{cases}

( 1 ) ( 2 ) : A 1 = 8 A π r 2 6 A 1 A 2 = 2 \begin{aligned} (1) - (2): \quad A_1 & = 8A - \frac {\pi r^2}6 & \implies \frac {A_1}{A_2} = \boxed 2 \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...